2008
DOI: 10.1590/s0004-282x2008000300008
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome in institutionalized elderly

Abstract: -Restless legs syndrome (RLS) is characterized by disturbing leg sensations associated to sleep complaints and excessive daytime somnolence. In the elderly, it affects 10 to 35%. Our objective was to determine the prevalence of RLS in institutionalized elderly, analyzing its relationship with clinical, laboratorial and neurophysiological features. We conducted a cross-sectional study of all the subjects under treatment on a chronic-care geriatric service by using face-to-face interviews, which include sleep co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
(28 reference statements)
0
5
0
6
Order By: Relevance
“…RLS as a one of the most intriguing chronic sensory-motor disorders is frequently unrecognized, misdiagnosed, and poorly managed [8, 21]. Awareness about RLS is poor among medical professionals and diagnosis of RLS was missed not only by general physicians, but also by specialists like neurologists and psychiatrists [2224].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RLS as a one of the most intriguing chronic sensory-motor disorders is frequently unrecognized, misdiagnosed, and poorly managed [8, 21]. Awareness about RLS is poor among medical professionals and diagnosis of RLS was missed not only by general physicians, but also by specialists like neurologists and psychiatrists [2224].…”
Section: Discussionmentioning
confidence: 99%
“…RLS symptoms are not reported by patients to their health care providers. So, identification and suitable management of RLS, especially in diabetic populations, are recommended [8, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…Sleep and fatigue in multiple sclerosis www.bjournal.com.br on primary care patients have initially shown a prevalence of RLS ranging from 5 to 15% in Caucasians (18)(19)(20)(21). Recently, larger population-based studies have reported lower incidences oscillating from 2-3% (22,23), 5-7% (24,25) to a maximum of 12% (26).…”
Section: Discussionmentioning
confidence: 99%
“…Uyku bozukluklarının olumsuz sonuçlarını azaltmak için toplum ve sağlık çalışanlarının farkındalığını artırma, uyku bozukluklarının tanılanması ve etkin yönetim için önemlidir [24]. Uyku bozuklukları olan bireyleri belirlerken, uykuyla ilgili bozuklukların 3 ana semptomun veya bunların kombinasyonun sorgulanması gerekir: uykusuzluk veya insomni, gündüz aşırı uykululuk veya hipersomni, gece içinde uyku ya da uyanıklıklar sırasında ortaya çıkan hareket veya davranışlardır [6,10,12,16,25]. Türkiye'de yaşlılarda uyku bozuklukları ile ilişkili semptomları, yaşlılarda uyku bozuklukları ile ilişkili faktörleri araştıran çok fazla çalışma bulunmamaktadır.…”
Section: Introductionunclassified